Is Post-activation performance enhancement real? Reliability of PAPE effects in professional volleyball players under complex training - Masel, S.; Maciejczyk, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Post-activation performance enhancement (PAPE) is a physiological phenomenon that is observed by an increased power output in an explosive exercise such as sprinting or jumping after applying a specific conditioning activity (CA) [1]. The phenomenon is often applied within complex training (CT) and various loading strategies and PAPE application methods may be implemented and acutely enhance subsequent post-CA performance [2,3] . However, authors tend to focus on introducing different study protocols without retesting the same experimental protocol in separate sessions. Thus, the aim of this study was to establish reliability of baseline to post-CA changes in three manners: 1) interday morning and afternoon reliability; 2) intraday morning and afternoon reliability; 3) intraday set-to-set reliability [4]. METHODS: Twelve professional male volleyball players (age: 22±2 years; volleyball training experience: 10.2±2.3 years, body height: 193.4±7.6, body mass: 84.1±8.1 kg) experienced in resistance training (7±1.6 years) participated in the study. They performed one familiarization session (1RM in a trap bar deadlift and squat jump (SJ) familiarization) and four identical experimental sessions (S1, S2, S3, S4). S1 and S3 were morning sessions and S2 and S4 were afternoon sessions, they were performed at the same time of the day. Sessions were performed twice in two days - S1 and S2 on the same day and S3 and S4 on the same day. During each experimental session participants performed mini complex training session - they performed three sets of a CA (3 repetitions of a trap bar deadlift at 80% 1RM with 15% of accommodating resistance) and 90s after a CA performed SJ with 4 minutes intra-set rest interval. The ANOVA with repeated measures was used to assess significance of the effect of a CA (significance was set at p<0,05) and ICC to assess reliability of measurements based on absolute-agreement 2-way mixed-effects model. RESULTS: During all trials, baseline to post-CA SJ changes were found to be repeatably insignificant in all sets. Interday morning (S1 and S3) reliability was moderate (ICC=0.67) and afternoon (S2 and S4) was good (0.8). Intraday morning and afternoon reliability was good for S1 and S2 (0.88) and poor for S3 and S4 (0.48). Intraday set-to set reliability was good for S1 (0.87), S2 (0.83), S3 (0.82) and moderate for S4 (0.58). CONCLUSION: This study provides a novel understanding of the PAPE phenomenon within CT. Results of this study suggest that the practitioners may effectively implement appropriately organized CT as both intraday set-to-set and interday morning and afternoon reliabilities seem to be acceptable. Implementing CT at both times of the day may be beneficial with a small advantage of afternoon sessions. However, introducing two CT sessions within one day is highly questionable as at the moment intraday morning and afternoon reliability is vague.